Black Lives Matter: Race Discourse and the Semiotics of History Reconstruction - Borysovych, Oksana Victorivna; Chaiuk, Tetyana Andriivna; Karpova, Kateryna Sergiivna (Journal of History Culture and Art Research, 2020)
The death of unarmed black male George Floyd, who was killed by a white police officer in Minneapolis, May 25, 2020, has given momentum to the Black Lives Matter (BLM) movement whose activists rallied in different parts of the world to remove or deface monuments to historic figures associated with racism, slavery, and colonialism. These social practices of toppling statues have a discursive value and, since they are meant to communicate a message to the broader society, these actions are incorporated into a semiotic system. This study examines signs and, therefore, the system of representations involved in toppling statues performed by BLM activists and documented in photos. The research employs a critical approach to semiotics based on Roland Barthes’ (1964) semiotic model of levels of signification. However, for a comprehensive analytical understanding, the study also makes use of a multidisciplinary Critical Discourse Analysis CDA approach which provides a systematic method to examine and expose power relations, inequality, dominance, and oppression in social practices. Besides its general analytical framework, the integrated CDA approach combines Fairclough’s (1995) three-dimensional analytical approach, which presupposes examining text, discursive practice, and sociocultural practice, with Reisigl and Wodak’s (2001, 2017) Discourse Historical Analysis (DHA), which investigates ideology and racism within their socio-cultural and historic context. The analysis of the images reveals a common thematic structure and encoded messages produced in order to change the cultural and social norms of the USA national discourse generated and cultivated within a specific ideological and historical context. These social actions consist of signs that make up a coherent communicative system which provides BLM activists with instruments in the struggle over the memory of slavery, white supremacy and oppression of the past for the rights of the black minority in the present in a better society of racial equality, human rights, and liberation.